Analisa Aplikasi E-Commerce Rupa-Rupa dengan Menggunakan Pendekatan Delone & McLean: Studi kasus pada aplikasi ruparupa - Muhammad Nur Hanifan; Rojuaniah Rojuaniah (MES Management Journal, 2026)
This research aims to determine the influence of product quality and location on purchasing decisions for coffeeshop products. This type of research is associative research. Data collection in this research was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 100 respondents, while the population used in this research was Hypermut coffeeshop customers. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis t ool used in this research uses SEM-PLS. The data analysis technique in this research is descriptive analysis, hypothesis testing using a partial significant test (t test), simultaneous significant testing (F test), and testing the coefficient of determinat ion (R2). The research results show that product quality and location have a positive and significant effect on purchasing decisions, both simultaneously and partially.